Self-Control and Disciplined Behavior Of Students - Miftahudh Dhiyya ‘Urrahma; Nur’aeni Nur’aeni (UM Purwokerto Press, 2021)
Islamic boarding school is a religious, educational institution with its characteristics and is different from other educational institutions. Education in Islamic boarding schools includes Islamic education, da’wah, community development, and additional similar education. This research aimed to determine the relationship between Self-Control with Discipline Behavior to students memorizing the Al-Qur’an at Islamic Boarding School Darussalam Purwokerto-Indonesia. This study uses quantitative research methods. The instrument used to collect data is the Self-Control scale and the Discipline Behavior scale. The population in the study was 80 students. Researchers use the entire population, so it is called population research. The data analysis technique uses product-moment correlation. Data were analyzed using Statistical Package for Social Sciences (SPSS) 25.0 for Windows Program. The results of the research data show that there is a relationship between Self-Control and Discipline Behavior in students who memorize the Qur’an at Islamic Boarding School Darussalam Purwokerto-Indonesia has a correlation of 0.695 and a significance level of p<0.01. The results of data analysis show that there is a positive relationship between Self-Control and Discipline Behavior.